Faktor-faktor yang Memengaruhi Kejadian Preeklampsia di RS Bhayangkara Polda Riau Provinsi Riau Tahun 2024 - Damayanty S; Ufi Alfianingsih; Erin Padilla Siregar; Novita Andriani Br. Manjorang; Ika Damayanti Sipayung; Ade Rachmat Yudiyanto (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The number of maternal deaths based on documentation of the family health program at the Ministry of Health, Indonesia had 4,627 deaths in 2020. This figure increased compared to 2019 which amounted to 4,221 deaths. Based on the cause, most maternal deaths in 2020 occurred due to bleeding (1,330 cases), pregnancy-related hypertension (1,110 cases), and circulatory system disorders (230 cases). Preeclampsia is associated with risk factors, including age; women over 40 are more likely to experience preeclampsia, as are mothers who are pregnant with many children. Using quantitative, using numerical data through retrospective surveys with cross-sectional studies. The population of all mothers who experienced preeclampsia in 2023-2024 amounted to 60 people, the research sample Total Sampling 60. The results of statistical tests showed that p.value = 0.004 and α = 0.05, where the value of P.value (0.004) <α (0.05), so it can be concluded that there is a relationship between maternal age and the incidence of Preeclampsia. The results of statistical tests showed that p.value = 0.019 and α = 0.005, where the value of P.value (0.019) <α (0.005), so it can be concluded that there is a relationship between maternal parity and the incidence of Preeclampsia. Based on the results of the statistical test, it was found that p.value = 0.000 and α = 0.05, where the value of P.value (0.000) < α (0.05), so it can be concluded that there is a relationship between maternal nutritional status and the incidence of preeclampsia. The results of the statistical test showed that p.value = 0.120 and α = 0.05, where the value of P.value (0.120) < α (0.05), so it can be concluded that there is no relationship between maternal gestational age and the incidence of preeclampsia.